Pena de ouro : escrevendo processos de educar e educar–se na roda de capoeira - Oliveira, Gilmar Araújo de (2016)
The main objective of this research was to identify, describe and understand the educative processes triggered in the relationship Master and Apprentice, in the context of Capoeira classes of the Cultural Association and Sports Pena de Ouro, taught by Master Izael Teixeira. The interest in researching educative processes resulting from Capoeira social practice is due to the search for the appreciation of knowledge produced by the Southern people, in the case, knowledge produced by black people who were enslaved, placed at the margins due to the colonization process of the southern countries geographical. In the context of this research, Capoeira is perceived as a manifestation of African origin gestated in the sphere of popular culture. The methodology used in the study was qualitative with inspiration in phenomenology, and data collection was performed with systematic records of observations in field diaries. In the construction of the results, the categories were presented: A) Educational of Master Izael B) Appreciation of the Master Izael by the Community and C) While rest, I carry Stone - Resistance and Ancestrally. We believe that the knowledge of the Master Izael extend beyond the Capoeira, enabling education for life. Educative processes related to the resistance and ancestrally were observed, which collaborate to the comprehension of the African worldview that is present in the lifestyle of african-brazilian population. These educative processes have the role to promote education for life in society and strengthen their African roots and identities.